Krzysztof Kieślowski’s film props in the triptych “Three Colours” - Otto, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Krzysztof Kieślowski employed film properties in a creative way in his Three Colours (Trois couleurs, 1993–94) trilogy. They play various roles in Blue (Bleu, 1993), White (Blanc, 1993) and Red (Rogue, 1994): they make the presented world more probable, co-create images of heroes, build dramaturgy and convey symbolic content. Such a treatment of film props is shaped by the director’s film style and creates a specific cinematic atmosphere.